Regulatory role of hippocampal PI3K and mTOR signaling pathway in NMDA-induced infant spasm rats. (2nd December 2019) - Yang, Guang; Wang, Jing; Wan, Lin; Shi, Xiu-Yu; Meng, Yan; Ren, Wei-Hua; Zou, Li-Ping
ABSTRACT: Objectives : To explore the role of mTOR signaling pathway in modulating epileptogenesis in an N-methyl-D-aspartic acid (NMDA)-induced infant spasm (IS) rat model. Methods : After inducing IS successfully, the phosphorylation status of PI3K, Akt, mTOR and S6K of brain and hippocampus tissues was assessed using western blot and immunochemistry analysis, respectively. The possible mechanism of mTOR signaling pathway was evaluated by the, inhibitors for mTOR and PI3K, rapamycin and wortmannin, respectively. The inhibitors were injected into the intraperitoneal space of the rats to examine the effects of PI3K and mTOR in IS rat model. Results : The phosphorylated levels of mTOR and PI3K in hippocampus increased significantly (P < 0.05) 7 days after IS induction in rats. After administration of wortmannin, the phosphorylated levels of PI3K and mTOR decreased. However, only the phosphorylated level of mTOR decreased obviously after rapamycin administration. No obvious neurogenesis was found after IS induction. Discussion : Results of the present study suggest that hippocampal PI3K may be another potential target for IS treatment.